Strategi Manajemen Informasi Iklan Layanan Masyarakat Keluarga Berencana (Studi Kasus di Dinas Pengendalian Penduduk, Pemberdayaan Perempuan dan Perlindungan Anak Kota Surabaya) - Rahmad Abadi Santoso (Universitas Negeri Surabaya, 2021)
This study aims to identify and explore the information management strategy of public service advertisements about Family Planning carried out by the Department of Population Control, Women's Empowerment, and Child Protection (DP5A) of Surabaya City. This study focuses on information management strategies for Public Service Advertisements about the Family Planning program and the latest advertisements of the BKKBN about